My child has a hard mass over the thigh / Shahrul Hisham Sulaiman - Sulaiman, Shahrul Hisham (Faculty of Medicine, 2024)
A 10-year-old boy was brought to the clinic by his parents, complaining of a palpable, slow growing hard mass over the distal left thigh for the past one year. There were no other swellings present on other parts of the body. His parents were worried since the swelling had increased in size over time. However, the child did not complain of any pain or any local pressure symptoms. He did not recall any obvious trauma to the limb. He did not have any constitutional symptoms. He was an active child and did not have any problems at school.